2005
DOI: 10.1002/lt.20559
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of low central venous pressure and phlebotomy on blood product transfusion requirements during liver transplantations

Abstract: Correction of coagulation defects with plasma transfusion did not decrease the need for intraoperative red blood cells (RBC) transfusions during liver transplantations. On the contrary, it led to a hypervolemic state that resulted in an increase of shed blood. As well, plasma transfusion has been associated with a decreased one-year survival rate. The aim of the present prospective survey was to evaluate whether anesthesiologists could reduce intraoperative RBC transfusions during liver transplantations by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
235
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(253 citation statements)
references
References 14 publications
5
235
1
3
Order By: Relevance
“…Almost all the points described by them have been well discussed in our article. 1 In response to some details they mentioned, we want to emphasize the main purpose of our study. It was to evaluate how we could transfuse less allogenic blood products in patients with comparable disease severity.…”
Section: To the Editorsmentioning
confidence: 99%
“…Almost all the points described by them have been well discussed in our article. 1 In response to some details they mentioned, we want to emphasize the main purpose of our study. It was to evaluate how we could transfuse less allogenic blood products in patients with comparable disease severity.…”
Section: To the Editorsmentioning
confidence: 99%
“…The first LTx was done in 1963 by Dr. Thomas Starzl and coworkers in Denver [1]. However, since 1980s advances in donor organ preservation, surgical techniques, patient selection, immunosuppressive regimens and treatments for opportunistic infections all have contributed to substantially improve the survival rates [2,3]. Currently survival rates of over 90-95 and 70 % respectively at 1 and 5 years post-LTx are common [4].…”
Section: Introductionmentioning
confidence: 99%
“…Implementing the same strategy to OLT, one study found that a low CVP increased morbidity as expressed as postoperative renal failure and mortality (Schroeder et al, 2004), while an other study came to the opposite conclusion (Massicotte et al, 2006). We hold it that volume therapy during OLT is better detected by flow related parameters than by vascular pressure(s) (Bundgaard-Nielsen et al, 2007a;Jenstrup et al, 1995;Ejlersen et al, 1995b).…”
Section: Vascular Pressuresmentioning
confidence: 93%